Analytical Survey of Development Directions of Social Labour Sphere of Urban Settlement - I.A., Polyakova; N.V., Tolstik (International Business and Accounting Research Journal, 2019)
The article shows the relevance of implementing the development processes and expanding the infoshere within the international standards of statistical accounting. It reflects methodological approaches to analytical processing of information resources characterizing  the conditions and trends in developing modern  urban settlement. The article also provides the dynamics on the a number of indexes  of social labour sphere in Rostov-on-Don. It shows the practicability of forming the conception of the strategic development of the urban settlement based on official information resources. The article provides the comparative assessment of   the position of Rostov-on-Don as the capital of the Southern Federal District on a number of indexes of social labour sphere regarding million-plus cities of Russian and regional capitals forming a part of the Southern Federal District.